Redesign Kantor Pemerintah Kabupaten Sumedang Divisi Administrasi Dengan Pendekatan Behaviour - Nurul Khalishah, Sarah; Nur Sheha Gunawan, Ahmad; Primiana Yuniati, Arnanti (Telkom University, 2024)
The Sumedang Regency Government Office is a government center and is the Regent's Office located at Jl. Prabu Gajah Agung No.19, Situ District, North Sumedang, Sumedang Regency, West Java 45621. This building has an area of 7,883m2 which has 3 floors, there are 193 employees who are divided into 3 assistants, one of whom is the General Administration assistant with 4 other sections, namely the General Section, Organization Section, Protocol & Leadership Communication Section, Planning & Finance Section. The Sumedang Regency Government Office has implemented SPBE (Electronic Based Government System) where in this application the current employee work system changes from using paper to conventional media (digital) this change needs to be accommodated because the activities, needs and working methods of employees are changing, from these changes it gives rise to employee behavior that requires better collaboration and communication, increases transparency and accountability, requires adaptation to technology. In addition, the implementation of SPBE at the Sumedang Regency Government Office must be adjusted to the cultural values of the Sumedang Regency Government Office, namely: Transparency, Responsibility and Effectiveness. The purpose of this project is to redesign the General Administration Assistant of the Sumedang Regency Government Office by considering the implementation of SPBE, office cultural values and changes in employee behavior into a design. Keywords: office, government, general administration.